CP-168 Obese patients: Are dose adjustments for treatment of comorbidities used?. (14th February 2016) - Paret, A; Roy, S; Courie, R; Rieutord, A; Decottignies, A
Abstract : Background: Obesity is associated with comorbidities requiring medicines. Although several pharmacokinetic changes are described in obese patients, few recommendations for dosage adjustments are available. Purpose: The aim of our study was to identify treatments introduced in a population of obese patients and to analyse recommendations in terms of treatments strategies and posology. Material and methods: Gathering information on the main treatments prescribed by a retrospective analysis of medical histories of patients hospitalised in 2014 for sleeve in a visceral surgery department. Literature review about therapeutic strategies or dosage adjustments to be made for the most prescribed molecules in this population. Results: 241 patients were included (85.9% female). Average age was 40.1 years ±11.7 and average body mass index was 43.3 (33–76). 153 patients (63, 5%) had at least one prescription. An average of 3.4 treatments by patient was found. The main medical comorbidities were: hypertension (50%), asthma (21%), gastric reflux (11%) and type 2 diabetes (11%). The most prescribed therapeutic classes in the patient population were: antihypertensives (21%), antiasthmatics (11%), proton pump inhibitors (PPIs) (9%) and oral antidiabetics (9%). All dosages were consistent with marketing authorisation. Very few recommendations for dose adjustments in obese patients were found in the literature and none concerned antihypertensives, antiasthmatics, PPIs or oral antidiabetics. For hypertension, inhibitors of the renin-angiotensin system and calcium channel blockers are preferred. 1 Recommended antihypertensive drugs were prescribed for 63.4% of our patients. Concerning PPIs, several studies recommended prescription of raberazole in obese patients but none of our patient received it. 2 Conclusion: The main comorbidities found in the studied population were consistent with the literature, and the most prescribed therapeutic classes matched these complications. Nevertheless, to ensure optimal management of treatment in this population, it is necessary that medical societies develop specific recommendations on treatment strategies and dosage adjustments. References and/or Acknowledgements: Wenzel UO, et al . Semin Nephrol 2013;33:66 Pace F, et al . Eur J Gastroenterol Hepatol 2011;23:845 No conflict of interest.